2016
DOI: 10.1007/s10103-016-2097-2
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of electromagnetic field and low-level laser increase proliferation and alter the morphology of human adipose tissue-derived mesenchymal stem cells

Abstract: In recent years, electromagnetic field (EMF) and low-level laser (LLL) have been found to affect various biological processes, the growth and proliferation of cells, and especially that of stem cells. The aim of this study was to investigate the effects of EMF and LLL on proliferation of human adipose tissue-derived mesenchymal stem cells (hAT-MSCs) and thus to examine the impact of these therapeutic physical modalities on stem cell engraftment. hAT-MSCs were isolated from subcutaneous adipose tissue of six pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…Khandra et al [33] showed there was increased cellular attachment, proliferation, differentiation, osteocalcin synthesis, and transforming growth factor β1 production in human osteoblast-like cells after low level laser irradiation. Nurković et al [21] demonstrated that PBMT accelerates MSC proliferation [21]. The results obtained were confirmed by the Gianellis team [34].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Khandra et al [33] showed there was increased cellular attachment, proliferation, differentiation, osteocalcin synthesis, and transforming growth factor β1 production in human osteoblast-like cells after low level laser irradiation. Nurković et al [21] demonstrated that PBMT accelerates MSC proliferation [21]. The results obtained were confirmed by the Gianellis team [34].…”
Section: Introductionmentioning
confidence: 84%
“…De Freitas and Hamblin consider that MSCs are particularly sensitive to low power laser irradiation, which causes increased gene expression, increased cell migration and proliferation, and accelerated production of antioxidant enzymes and anti‐apoptotic proteins. Nurkowić et al showed that after application of an electromagnetic field (EMF) (time, 30 min; frequency ‐50 Hz, intensity ‐3 mT for 7 days) and low level laser therapy (time, 5 min; energy density, 3 J/cm 2 ; wavelength, 808 nm; power density, 200 mW/cm 2 for 7 days) there were more MSCs than in untreated samples, with the biggest increase resulting from concurrent application of EMF and PBMT . Gianelli et al indicated that laser irradiation (power, 0.89 W; wavelength, 635 nm; continuous emission) stimulates MSC proliferation associated with increased membrane conductance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biostimulating effects of this technique are achieved when a specific wavelength of light is absorbed by the photoreceptors of the irradiated cells [14]. A wide network of intracellular signaling cascades are then triggered, leading to various biological effects in promoting cell growth and survival, proliferation, collagen synthesis, and differentiation [15][16][17][18]. Studies have reported that LPLI exerts biostimulating effects on osteogenic cells and bone tissues in vitro [15,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%